CoP and vection variables for 19 subjects with varying visual field and amplitude conditions - Horiuchi, Kentaro (Tokyo Metropolitan University, 2021)
This repository contains data from a study to investigate possible effects of vection on postural control. The data contain two variables (anterior-posterior displacement and total length of trajectory) describing posture, and three variables (rating, latency and duration) describing vection. The experiment used three visual field conditions and five amplitude conditions; posture and vection variables are available for each condition. See Horiuchi et al. (2021) for details.

The data set comprises posture and vection data collected from 19 participants using a Wii fit board and Wii remote. The variables presented in the data set have been calculated from the raw data (see technical document for information). The experiment used 15 experimental conditions, and the variables are presented for each participant in each condition.

Data från en studie där man mätt om upplevd känsla av rörelse påverkar kroppshållningen. Datan innehåller två variabler för kroppens rörelse och tre variabler för upplevelse av rörelse. För mer information, se Horiuchi et al. (2021).
CoP and vection variables for 19 subjects with varying visual field and amplitude conditions
Keywords: Visual Perception; Synuppfattning; Posture; Kroppshållning; Postural Balance; Postural balans; Psychological Phenomena; Psykologiska fenomen; Visual Fields; Synfält; Health Sciences; Hälsovetenskap; Psychology; Psykologi